Heavy Metal Contamination of Water and Soil 2014
DOI: 10.1201/b16566-8
|View full text |Cite
|
Sign up to set email alerts
|

Human Exposure Pathways of Heavy Metals in a Lead-Zinc Mining Area, Jiangsu Province, China

Abstract: Heavy metal pollution is becoming a serious issue in developing countries such as China, and the public is increasingly aware of its adverse health impacts in recent years. We assessed the potential health risks in a lead-zinc mining area and attempted to identify the key exposure pathways. We evaluated the spatial distributions of personal exposure using indigenous exposure factors and field monitoring results of water, soil, food, and indoor and outdoor air samples. The risks posed by 10 metals and the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
3
10
2
Order By: Relevance
“…1), indicating children living much closer to the coking plant were more likely to experience lead exposure. Similar decreasing trend from the source location was previously reported in other studies in a leadzinc mining area (Qu et al, 2012) and an e-waste recycling town in China (Zheng et al, 2008). It is worth mentioning that, the highest blood lead concentration occurred to the child who living 2 km away from the coking plant, could be mainly attributed to the reason that the family was located downwind the coking plant.…”
Section: Blood Lead Levels Of Children Living Around Coking Areasupporting
confidence: 85%
“…1), indicating children living much closer to the coking plant were more likely to experience lead exposure. Similar decreasing trend from the source location was previously reported in other studies in a leadzinc mining area (Qu et al, 2012) and an e-waste recycling town in China (Zheng et al, 2008). It is worth mentioning that, the highest blood lead concentration occurred to the child who living 2 km away from the coking plant, could be mainly attributed to the reason that the family was located downwind the coking plant.…”
Section: Blood Lead Levels Of Children Living Around Coking Areasupporting
confidence: 85%
“…Inhalation exposure and dermal contact contributed little. Compared with a previous study (Qu et al, 2012), the results found that the contribution of different exposure pathways was similar to the village in the previous study which was closest to the mine area. The local children's exposure to As mainly occurred through staple food ingestion and indoor air inhalation exposure, and home indoor air contributed more than school indoor air (Fig.…”
Section: Non-cancer Risksupporting
confidence: 73%
“…Compared with previous results (Qu et al, 2012), except for the site-specific contaminants and lifestyle, the higher non-carcinogenic risks in this study could also be explained by the fact that more toxic metal(loid)s in the integrated exposure pathway were taken into consideration for the health effect in this study. Furthermore, based on the questionnaire-survey on the dietary and behavior patterns, the children preferred local food, which has relative higher contents of heavy metals and metalloids.…”
Section: Non-cancer Riskcontrasting
confidence: 72%
See 2 more Smart Citations